KAJIAN EKONOMI USAHATANI HORTIKULTURA PADA KELOMPOK WANITA TANI PERKOTAAN DI BOGOR - Anak Agung Eka Suwarnata; Nia Sonani; Agista Rosiana (Universitas Galuh Ciamis, 2021)
The role of farmer groups in urban areas is very much needed in the development of horticultural commodities because it is estimated that the demand for horticultural commodities will increase as the population increases. This is certainly a good business opportunity for urban farmers, especially urban female farmer groups (KWT). The purpose of this research is to examine economically horticultural farming in urban KWT in Bogor in terms of income aspects and the efficiency of using farm costs. The research location was at 52 KWT Bogor City from June-November 2020. Collecting data using questionnaires, survey techniques, interview observation, and documentation study. The study used farm income analysis, while the efficiency analysis was measured by the R/C ratio. The results of the economic study showed that the average cash income of horticultural farming at KWT in Bogor per year per area of 487 m2 was IDR 3,514,080.75 or equivalent to IDR 7,203,865.55 / year / 10 are, while the average total income worth IDR 1,190,686.16 per 487 m2 or equivalent to IDR 2,440,906.62 / year / 10 are. The R / C value of the ratio of cash costs is 4.24, and the R / C ratio of total costs, the value is 1.37, which means that horticultural farming in KWT in Bogor is efficient to run because the targeted input compared to the actual input is greater or equal to one.